Kitâb Nehcü’l-belâga el-câmi’ li hutab ve hikem ve resâ’il emîrü’l-mü’minîn Ebu’l-Hasan Ali b. Ebû Talib - 880-01 Ebu’l-Hasan Ali b. Ebû Talib. (Mısır)
5 cilt (Fihrist 59 sayfa ; 1. c. 506 sayfa ; 2. c. 598 sayfa ; 3. c. 499 sayfa ; 4. c. 576 sayfa)